2021
DOI: 10.1080/2162402x.2021.1887552
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-mediated communication between tumor cells and tumor-associated macrophages: implications for tumor microenvironment

Abstract: Exosomes are extracellular vesicles released from numerous types of cells that are involved in multiple tumors development. Exosomes contribute to the modulation of tumor microenvironment (TME) through intercellular communication. As essential immune stromal cells in the TME, tumor-associated macrophages (TAMs) participate in tumor development by mediating angiogenesis, metastasis, chemoresistance, and immune escape. Due to communication with multiple cells in the TME, they exhibit plasticity and heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 168 publications
1
50
0
Order By: Relevance
“…Extracellular release of KRAS G12D by cancer cells succumbing to autophagy‐dependent ferroptosis is essential for pancreatic tumor‐associated macrophages (TAM) to switch to an “M2‐like” immunosuppressive phenotype (Dai et al , 2020 ). Importantly, M2 TAMs have been linked to tumor progression, metastases (Han et al , 2021 ), and resistance to conventional chemotherapeutics (Larionova et al , 2019 ) in multiple tumors. Consistent with this finding, chloroquine and its derivative hydroxychloroquine improve TAM‐mediated anticancer immune response by promoting the establishment of an “M1‐like” phenotype (Chen et al , 2018a ; Sharma et al , 2020 ).…”
Section: Cancermentioning
confidence: 99%
“…Extracellular release of KRAS G12D by cancer cells succumbing to autophagy‐dependent ferroptosis is essential for pancreatic tumor‐associated macrophages (TAM) to switch to an “M2‐like” immunosuppressive phenotype (Dai et al , 2020 ). Importantly, M2 TAMs have been linked to tumor progression, metastases (Han et al , 2021 ), and resistance to conventional chemotherapeutics (Larionova et al , 2019 ) in multiple tumors. Consistent with this finding, chloroquine and its derivative hydroxychloroquine improve TAM‐mediated anticancer immune response by promoting the establishment of an “M1‐like” phenotype (Chen et al , 2018a ; Sharma et al , 2020 ).…”
Section: Cancermentioning
confidence: 99%
“…Emerging evidence has suggested that the communication between tumor cells and macrophages plays a key role in mediating TAM polarization [ 14 , 15 ]. Signals originated from tumor cells such as transforming growth factor beta (TGF-β), could promote differentiation of non-activated macrophages into a TAM-like immunosuppressive phenotype characterized as increased anti-inflammatory cytokine and decreased pro-inflammatory cytokine expression [ 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage-derived EVs have multiple functions depending on various phenotypes of parental cells. Both endogenous and exogenous stimulatory factors influence the secretion of macrophage-derived EVs ( 62 ). Lysosomes can fuse with multivesicular bodies to determine their trafficking pathway.…”
Section: Innate Immune Cell-derived Evsmentioning
confidence: 99%